Pengaruh Fasilitas Belajar Dan Kesesuaian Kurikulum Terhadap Minat Siswa SMK Swasta Melanjutkan Ke Perguruan Tinggi - Marlinda, Marlinda; Harapan, Edi; Fahmi, Muhammad (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to determine the effect of learning facilities and curriculum suitability on the students' interest of private vocational high school at Ogan Komering Ilir Regency in continuing their studies to higher education. In this study, 217 samples were taken randomly from each school. 42% of each school was taken to fulfill minimum number of samples. This study used multiple correlational method by analyzing the relationship between variables, by testing the instruments through testing validity and reliability. The results of the study showed that there was correlation between learning facilities (X1) and curriculum suitability (X2) with the students’ interests of private vocational high school at Ogan Komering Ilir Regency in continuing to higher education (Y) of 0.627a; so the value indicates the category of relationship was